2014
DOI: 10.1371/journal.pone.0105174
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multi-Species Biotic Ligand Model Predicting the Toxicity of Trivalent Chromium to Barley Root Elongation in Solution Culture

Abstract: Little knowledge is available about the influence of cation competition and metal speciation on trivalent chromium (Cr(III)) toxicity. In the present study, the effects of pH and selected cations on the toxicity of trivalent chromium (Cr(III)) to barley (Hordeum vulgare) root elongation were investigated to develop an appropriate biotic ligand model (BLM). Results showed that the toxicity of Cr(III) decreased with increasing activity of Ca2+ and Mg2+ but not with K+ and Na+. The effect of pH on Cr(III) toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…According to this model, the binding of Cr(III) to the cell wall is based on metal speciation and competitive binding between Cr(III) species and H þ of cell wall functional groups, commonly called "biotic ligands." Acid pHs increase the solubility and availability of Cr(III) species (e.g., Cr 3þ and CrOH 2þ ) but also increase the concentration of free H þ in root surrounding solution, leading to increased competition between Cr(III) species and free H þ for cell wall binding sites (Song et al 2014). As the pH is increased, the concentration of free H þ decreases and the surface charge density of the root cell wall becomes negative (Chathuranga et al 2013) 3A and B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this model, the binding of Cr(III) to the cell wall is based on metal speciation and competitive binding between Cr(III) species and H þ of cell wall functional groups, commonly called "biotic ligands." Acid pHs increase the solubility and availability of Cr(III) species (e.g., Cr 3þ and CrOH 2þ ) but also increase the concentration of free H þ in root surrounding solution, leading to increased competition between Cr(III) species and free H þ for cell wall binding sites (Song et al 2014). As the pH is increased, the concentration of free H þ decreases and the surface charge density of the root cell wall becomes negative (Chathuranga et al 2013) 3A and B).…”
Section: Discussionmentioning
confidence: 99%
“…The main assumption of the BLM is that metal toxicity is caused by free metal ions reacting with biological binding sites (Ardestani et al ). According to this model, the binding of Cr(III) to the cell wall is based on metal speciation and competitive binding between Cr(III) species and H + of cell wall functional groups, commonly called “biotic ligands.” Acid pHs increase the solubility and availability of Cr(III) species (e.g., Cr 3+ and CrOH 2+ ) but also increase the concentration of free H + in root surrounding solution, leading to increased competition between Cr(III) species and free H + for cell wall binding sites (Song et al ). As the pH is increased, the concentration of free H + decreases and the surface charge density of the root cell wall becomes negative (Chathuranga et al ) so that more cationic species (e.g., Cr[OH] 2+ and Cr[OH] 2 + ) and even polyhydroxyl species (e.g., Cr 2 [OH] 2 4+ and Cr 4 [OH] 4 5+ ) can bind to plant roots.…”
Section: Discussionmentioning
confidence: 99%
“…An application of the biotic ligand model to the study of root elongation in barley (Song et al 2014) suggested Cr 3þ and Cr(OH) 2þ as the 2 biologically active chemical species in controlling the effects of Cr III . An application of the biotic ligand model to the study of root elongation in barley (Song et al 2014) suggested Cr 3þ and Cr(OH) 2þ as the 2 biologically active chemical species in controlling the effects of Cr III .…”
Section: Implications For Cr Hazard and Risk Assessmentmentioning
confidence: 99%
“…Furthermore, subsequent to our IC-ICP-MS results, the question of the actual Cr III species responsible for the observed ecotoxicological effects in living organisms deserves additional study. An application of the biotic ligand model to the study of root elongation in barley (Song et al 2014) suggested Cr 3þ and Cr(OH) 2þ as the 2 biologically active chemical species in controlling the effects of Cr III . However, the rapid disappearance (< 2 h) of ionic Cr from the test medium questions the role of such species in determining the shown algal response.…”
Section: Implications For Cr Hazard and Risk Assessmentmentioning
confidence: 99%
“…Chromium (Cr) occurs in the environment primarily in two common oxidation states: Cr(III) and Cr(VI) [ 15 ]. It is a beneficial micronutrient and has shown significant anti-diabetic activity [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%